Neuropeptide regulation of adaptive immunity in the tibia fracture model of complex regional pain syndrome - Li, Wen-Wu (J Neuroinflammation, 2018)
BACKGROUND: Both dysfunctional neuropeptide signaling and immune system activation are characteristic of complex regional pain syndrome (CRPS). Unknown is whether substance P (SP) or calcitonin gene-related peptide (CGRP) support autoantibody production and, consequently, nociceptive sensitization. METHODS: These experiments involved the use of a well-characterized tibia fracture model of CRPS. Mice deficient in SP expression (Tac1(−/−)) and CGRP signaling (RAMP1(−/−)) were used to probe the neuropeptide dependence of post-fracture sensitization and antibody production. The deposition of IgM in the spinal cord, sciatic nerves, and skin was followed using Western blotting, as was expression of the CRPS-related autoantigen cytokeratin 16 (Krt16). Passive serum transfer to B-cell-deficient muMT mice was used to assess the production of functional autoantibodies in CRPS model mice. The use of immunohistochemistry allowed us to assess neuropeptide-containing fiber distribution and Langerhans cell abundance in mouse and human CRPS patient skin, while Langerhans cell-deficient mice were used to assess the functional contributions of these cells. RESULTS: Functional SP and CGRP signaling were required both for the full development of nociceptive sensitization after fracture and the deposition of IgM in skin and neural tissues. Furthermore, the passive transfer of serum from wildtype but not neuropeptide-deficient mice to fractured muMT mice caused enhanced allodynia and postural unweighting. Langerhans cells were increased in number in the skin of fracture mice and CRPS patients, and those increases in mice were reduced in neuropeptide signaling-deficient animals. Unexpectedly, Langerhans cell-deficient mice showed normal nociceptive sensitization after fracture. However, the increased expression of Krt16 after tibia fracture was not seen in neuropeptide-deficient mice. CONCLUSIONS: Collectively, these data support the hypothesis that neuropeptide signaling in the fracture limb of mice is required for autoantigenic IgM production and nociceptive sensitization. The mechanism may be related to neuropeptide-supported autoantigen expression.